DEVELOPMENT OF THE POTAR BUNGKERLA MEDIA TO DISCOVER THE VOLUME FORMULAS IN GRADE VI AT MIN 22 ACEH BESAR - Nida Jarmita; Zikra Hayati; Rachmawati Rachmawati; Muhammad Afif Narfi (PIONIR: JURNAL PENDIDIKAN, 2025)
Teachers need a simple teaching aid that aligns with the topic of three-dimensional shapes and can be reused over a long period. This research is motivated by students' difficulties in understanding the elements of three-dimensional shapes, as well as their confusion in determining the volume formulas of curved-sided solids that are relatively similar. Therefore, this study aims to develop an appropriate instructional media to help address these student learning difficulties. Therefore, research and development are necessary to produce the Potar Bungkerla media, which is adapted from the environment. R&D (Research and Development) with a model ADDIE (analysis, design, development, implementation and evaluation) used in this research. The instruments consist of expert validation sheets for media and content experts, as well as teacher and student response questionnaires. The final results obtained from media expert validation scored 93.6%, while content expert validation scored 83%, both classified as "highly feasible." Meanwhile, the teacher response scored 95% with a "very interesting" classification, and the student response scored 88.75%, also classified as "very interesting." As a result, this study successfully developed a learning media that can be used by students to overcome difficulties in discovering the volume formulas of curved-sided solids. These figures indicate that this media is highly feasible and captures students' interest. Therefore, the research has been completed, and the media can be used in Grade VI at MIN 22 Aceh Besar. Keywords: Potar Bungkerla Media, Curved-Surface Three-Dimensional Shapes.